2021
DOI: 10.1111/aphw.12284
|View full text |Cite
|
Sign up to set email alerts
|

Adhering to COVID‐19 health guidelines: Examining demographic and psychological predictors of adherence

Abstract: The effort to limit the spread of the coronavirus (COVID‐19) has relied heavily on the general public's compliance with health guidelines limiting social contact and mitigating risk when contact occurs. The aim of this study was to identify latent variables underlying adherence to COVID‐19 guidelines and to examine demographic and psychological predictors of adherence. A sample of US adults ( N = 1,200) were surveyed in late April to mid‐May 2020. The factor structure of adherence was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 62 publications
3
21
0
Order By: Relevance
“…• Encourage patients to restrict social contact to reduce risk of infection 97 • Prioritise patients for vaccination 98,99 • Encourage patients to incorporate a healthy lifestyle during lockdown and quarantine 22 • Individual management: help patients to establish an individual set of selfmanagement goals (eg, measurement rate, bodyweight, steps per day, waist circumference, blood pressure) and to adhere to these goals consistently 100 • Digital support: help patients to make use of online education, virtual consultation, and digital health (eg, measurements of temperature, physical activity, bodyweight, waist circumference, and blood pressure, which will be digitally transferred to the physician) 101 • Behavioural support: help patients to use digital stress management tools to increase resilience and stress resistance 102 • Intensify foot care 103 • Check for new diabetes 90 • Manage cardiac risk 9 • Encourage patients to adhere to lipid-lowering drugs 40,77 • Monitor urinary excretion and oedema in patients with chronic kidney disease 12 • Optimise metabolic and blood pressure control 101 • Perform intensified glucose monitoring (eg, self-monitoring of blood glucose five times per day, flash and continuous glucose monitoring) to identify early deterioration of glycaemic condition and monitor blood pressure if…”
Section: Reviewmentioning
confidence: 99%
“…• Encourage patients to restrict social contact to reduce risk of infection 97 • Prioritise patients for vaccination 98,99 • Encourage patients to incorporate a healthy lifestyle during lockdown and quarantine 22 • Individual management: help patients to establish an individual set of selfmanagement goals (eg, measurement rate, bodyweight, steps per day, waist circumference, blood pressure) and to adhere to these goals consistently 100 • Digital support: help patients to make use of online education, virtual consultation, and digital health (eg, measurements of temperature, physical activity, bodyweight, waist circumference, and blood pressure, which will be digitally transferred to the physician) 101 • Behavioural support: help patients to use digital stress management tools to increase resilience and stress resistance 102 • Intensify foot care 103 • Check for new diabetes 90 • Manage cardiac risk 9 • Encourage patients to adhere to lipid-lowering drugs 40,77 • Monitor urinary excretion and oedema in patients with chronic kidney disease 12 • Optimise metabolic and blood pressure control 101 • Perform intensified glucose monitoring (eg, self-monitoring of blood glucose five times per day, flash and continuous glucose monitoring) to identify early deterioration of glycaemic condition and monitor blood pressure if…”
Section: Reviewmentioning
confidence: 99%
“…There are numerous studies describing and investigating compliance with Covid-19 measures in various countries, particularly for the US [2][3][4][5][6][7], Germany [8], Italy [9], Switzerland [1,10], Slovakia [11], Israel [12], South Korea [13], Japan [14], Indonesia [15], or Co ˆte d'Ivoire [16]. Even though many of these studies only use opportunity samples or student samples, a few consistent results have still emerged.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Less consistent are the findings concerning age. Most studies report that younger people are less inclined to comply with Covid-19 measures [5,11], but there is also opposing evidence [2,4,14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The extent to which individuals have been conforming to stay-at-home orders and other protective measures and which are the best predictors of individuals' adherence is less clear and remains a public health priority [8,9]. Prior research focused on the general population evidenced that women [8][9][10][11][12][13], people who live with others [14], and the unemployed [8,13,15] adhere more to behavioral restrictions than men, people living alone, and the employed.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the studies reported above, a series of hypotheses were made regarding the potential predictors of adherence. Regarding sociodemographic indicators, we hypothesized that women [8][9][10][11][12][13], people who live with others [14], and the unemployed [8,13,15] might report higher adherence to government restrictions. Moreover, recalling the interrelation between health behavior patterns [31][32][33], we hypothesized that people who worsened their lifestyles during the pandemic might be less willing to follow the rules.…”
Section: Introductionmentioning
confidence: 99%